Preclinical Pharmacokinetics and Pharmacology Study of RC98: A Programmed Cell Death Ligand 1 Monoclonal Antibody in Cynomolgus Monkeys - Wang, Ling; Li, Qiaoning; Deng, Chenglian; Liu, Zhihao; Wang, Fang; Li, Shenjun; Dong, Lihou; Jiang, Jing (Current Pharmaceutical Design, 2024)
Introduction: RC98 is the monoclonal antibody against Programmed Cell Death Ligand 1 (PD-L1). Relevant reports have confirmed that the influence of PD-L1 expressed by tumor cells on antitumor CD8+ T cell responses is well characterized, but the impact of PD-L1 expressed by immune cells has not been well defined. Objective: This study aimed to design a Pharmacokinetics/Pharmacology (PK/PD) study of RC98 in normal cynomolgus monkeys to research the effect on the immune system. Methods: RC98 and vehicle were administered to cynomolgus monkeys at 15 mg/kg via intravenous infusion once a week for 4 weeks to evaluate the relationship between PK and PD. The pharmacodynamic activity was measured by the PD-L1 receptor occupancy (RO) in CD3+ T cells, A T-cell-dependent antibody response (TDAR), and the concentration of soluble PD-L1. Results: The pharmacokinetic result showed that the exposure from the last administration was lower than that of the first administration, probably due to immunogenicity production. There was a strong correlation between systemic exposure and RO in CD3+ T cells but decreased RO levels after the last dose, which indirectly reflected the activation of T cells. The keyhole limpet hemocyanin (KLH)-induced TDAR in the RC98 group was higher than in the vehicle group. The concentration of soluble PD-L1 had increased feedback with RC98, and the concentration of soluble PD-L1 was maintained at a higher level after multiple doses than before dosing. Conclusion: These data indicate that the immune system was clearly activated. In addition, the non-clinical data could provide a basis for its efficacy evaluation in clinical trials.
Keywords: pharmacokinetic